Unklab Economics and Business Students’ Mispronunciation of English Words with Silent Letters - B, Lumoindong; Salainti, E (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The goal of this research was to find the types of mispronunciation made by the economics and business students of Universitas Klabat in Pre Intermediate 2 class of 2025/2026 academic year. It used the quantitative research method by taking 14 students from the total population of 28. The test of pronunciation skill and interview were implemented as the instruments of this research. The researcher used 10 sentences for the students to read one by one in a slow pace. Each of them contains particular English word with silent letter to identify if the student could read them well. The students were not allowed to repeat their pronunciations. Every silent letter will just appear once in every sentence. The results of the research showed that the students would always make two types of errors, which are pre-systematic errors and systematic errors. The number of occurrences of pre-systematic error is more than the other one. The highest error made by the students were the words with silent letters “b” (e.g. plumber) and “p” (e.g. psychology) where total numbers of errors for both letters were 56 (40%). The conclusion of this research was the students faced pronunciation issues with words that contain silent letters that were used in different ways in their mother tongue language.